An Error Analysis In Learning The Simple Present Tense By The 7th Grade Students Of SMP Swasta Al Washliyah 27 Medan - Siti Rohana, Yulia Sari Harahap (Pusdikra Publishing, 2022)
Simple Present Tense is part of English language grammar that stated in tenses. It expresses action in daily activities and general truth. The purposed of this research is to analyze errors in learning simple present tense. The errors analyzed in this research are: error of omission, addition, misformation and misordering. The method of this research approach is descriptive qualitative. It was conducted at SMP Al washliyah 27 Medan, the sample was taken from 20 students in the 7th grade of their written test. After analyzing and locating the errors from their answer sheets. The researcher found some finding of the research. The types of errors made by the students on learning the simple present tense are based on surface strategy taxonomy which are classified into omission, addition, misformation and misordering. After counting the errors, the researcher found 317 total of errors which consist of 50 errors of omission, 39 error of addition, 132 errors of misformation and 96 errors of misordering. From the data above it can be seen that misformation error was the highest number of error made by the students and following by misordering of error. At SMP Swasta Al Washliyan 27 Medan, the researcher also can find some causes of errors. They are Interference and teacher-induced error. Interference is error that are influenced by the interference of students mother tongue. The students still apply indonesian pattern into English when they translate the sentences. Then, Teacher-induced errors which teacher's teaching method required to be enhance and adequate to make the students have interest in learning English language.